The Relationship Between Thinking Styles and Writing Achievement of The Eleventh Graders of SMA Islam AZ-ZAHRA Palembang - Dafa, Fadhilah; Aditya , Andi; Budiyanto , Darmawan; Ridho, M Rasyid (Journal of English Education, 2023)
This study aimed to find out the relationship between thinking styles and writing achievement, how much thinking styles contributed to the students’ writing achievement. This study used correlational research design. The sample was selected by using purposive sample technique, consisting of 55 students. The data were collected by administering thinking styles questionnaire and writing achievement test. The data obtained were analyzed by using Pearson Product Moment and Regression significant relationship between thinking styles and writing achievement of the eleventh graders of SMA Islam Az-Zahra Palembang and it categorized as low correlation. Moreover, thinking styles strategy contributed as much 31%. This means that the significant value of the correlation was included in the low category. In addition, the significant coefficient was -0.176 lower than alpha value 0.05 there was no significant correlation. The Pearson Correlation of students’ thinking styles and writing achievement was 0.199 indicates in low category correlation. It means the correlation coefficient was found to be insignificant. It also implies there was no statistically significant relationship between thinking styles and their writing achievement. The null hypothesis (Ho) was accepted and the alternative hypothesis (Ha) was rejected, as determined by the writer.